A Multi‐Instrument Study of a Dipolarization Event in the Inner Magnetosphere. Issue 5 (10th May 2021) - Matsui, H.; Torbert, R. B.; Spence, H. E.; Argall, M. R.; Cohen, I. J.; Cooper, M. B.; Ergun, R. E.; Farrugia, C. J.; Fennell, J. F.; Fuselier, S. A.; Gkioulidou, M.; Khotyaintsev, Yu. V.; et al.
Abstract: A dipolarization of the background magnetic field was observed during a conjunction of the Magnetospheric Multiscale (MMS) spacecraft and Van Allen Probe B on September 22, 2018. The spacecraft were located in the inner magnetosphere at L ∼ 6–7 just before midnight magnetic local time (MLT). The radial separation between MMS and Probe B was ∼1 R E . Gradual dipolarization or an increase of the northward component B Z of the background field occurred on a timescale of minutes. Exploration of energization and Radiation in Geospace located 0.5 MLT eastward at a similar L shell also measured a gradual increase. The spatial scale was of the order of 1 R E . On top of that, MMS and Probe B measured B Z increases, and a decrease in one case, on a timescale of seconds, accompanied by large electric fields with amplitudes > several tens of mV/m. Spatial scale lengths were of the order of the ion inertial length and the ion gyroradius. The inertial term in the momentum equation and the Hall term in the generalized Ohm's law were sometimes non‐negligible. These small‐scale variations are discussed in terms of the ballooning/interchange instability and kinetic Alfvén waves among others. It is inferred that physics of multiple scales was involved in the dynamics of this dipolarization event. Key Points: A dipolarization was observed during a conjunction of Magnetospheric Multiscale and Van Allen Probe B in the inner magnetosphere A B Z increase on a timescale of minutes was overlaid with those on a timescale of seconds The inertial term and the Hall term sometimes played a role during B Z increases on a timescale of seconds